Estudio léxico del garífuna: Sinonimia y préstamos léxicos - Sánchez Pineda, María Trinidad (2018)
Two lexical fields of the Garifuna language were taken into account for this study: flora and fauna. Both quantitative and qualitative methodologies were used. The sample consisted of ten informants, all of them older than thirty. As the intention was to obtain synonyms and lexical borrowings of names of plants and animals, we asked questions using a certain vocabulary. The results showed the preponderance of Hispanisms in the Garifuna language.